2020
DOI: 10.3389/fimmu.2020.01592
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Response to PAMPs of Human Monocyte-Derived Foam Cells Obtained by Long-Term Culture in the Presence of oxLDLs

Abstract: Cholesterol-laden, foam macrophages constitute the most characteristic component of human atherosclerotic plaques. Persistent uptake of oxLDLs results in accumulation of lipid bodies inside the cells and determines their phenotype and subsequent functions. In this work, we describe the phenotype of human monocyte-derived foam cells obtained by differentiation in the constant presence of oxLDLs for 30 days (prolonged-hMDFCs). Although neither the total cellular nor the cell surface expression of Toll-like recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Notably, miR-155 regulates multiple cell death pathways, as macrophage derived miR-155 containing exosomes enhanced pyroptosis in cardiomyocytes through the direct targeting of FoxO3a (63). Human monocyte derived foam cells, obtained after prolonged exposure to oxidized LDL [a known inducer of miR-155 expression (46,64)], respond to inflammasome activation preferentially with pyroptosis combined with other types of necrotic death (65). Thus, it could be speculated that switching between cell death pathways is an effector mechanism of miR-155 as these pathways have the capacity to regulate the immunogenic cell death burden which can contribute to atherosclerosis development.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, miR-155 regulates multiple cell death pathways, as macrophage derived miR-155 containing exosomes enhanced pyroptosis in cardiomyocytes through the direct targeting of FoxO3a (63). Human monocyte derived foam cells, obtained after prolonged exposure to oxidized LDL [a known inducer of miR-155 expression (46,64)], respond to inflammasome activation preferentially with pyroptosis combined with other types of necrotic death (65). Thus, it could be speculated that switching between cell death pathways is an effector mechanism of miR-155 as these pathways have the capacity to regulate the immunogenic cell death burden which can contribute to atherosclerosis development.…”
Section: Discussionmentioning
confidence: 99%
“…It also promotes necrotic core formation in advanced atherosclerosis. In vitro study shows that low-concentration ox-LDL treatment induces pyroptosis in human monocyte-derived foam cells ( 107 , 108 ). Absent in melanoma 2 (AIM2)-dependent macrophage pyroptosis exacerbates atherosclerosis as well.…”
Section: Consequences Of Foam Cells In Atherosclerosismentioning
confidence: 99%
“…Actually, the high concentration of TNF-α released after treatment with CitH3 and H3 can also induced other lytic cell death like necroptosis ( 53 ). Interestingly, a recent study showed that prolonged exposure of myeloid cells to DAMPs like oxLDLs can induce cell to switch between cell death pathways ( 54 ). CitH3 and H3 may also activate different cell death pathways simultaneously or undergo a transition between different cell death pathways.…”
Section: Discussionmentioning
confidence: 99%